Correction: Design and characterisation of bodipy sensitizers for dye-sensitized NiO solar cells. Issue 4 (5th January 2016) - Summers, Gareth H.; Lefebvre, Jean-François; Black, Fiona A.; Davies, E. Stephen; Gibson, Elizabeth A.; Pullerits, Tönu; Wood, Christopher J.; Zidek, Karel
Abstract : Correction for 'Design and characterisation of bodipy sensitizers for dye-sensitized NiO solar cells' by Gareth H. Summers et al., Phys. Chem. Chem. Phys., 2016, DOI: ; Web:10.1039/c5cp05177k .